Destino del Crédito de Desarrollo Humano y su impacto en el rendimiento de los emprendimientos - Maza Chamba, Roosbelt Bryan (2023)
In Ecuador, the State provides financial access through the program called "Desarrollo Humano" credit (CDH as its abbreviation in Spanish), a tool applied as a strategy to overcome poverty. This credit aims to create opportunities to promote the creation of microenterprises in order to improve the quality of life of Ecuadorian families living in poverty and extreme poverty. This research aims to evaluate the use of CDH and its impact on business performance. A quantitative study was used, using the ANOVA test to analyze the hypothesis that there are no differences in the performance of the enterprises in relation to the intended activity they are going to use the credit for. For that reason, 246 surveys were applied to a population sample of CDH beneficiaries from the database of the Ministry of Economic and Social Inclusion. The main results show that there is a higher concentration of CDH beneficiaries in Sucre parish, with the female gender having greater access to the program. Likewise, among the main economic activities in which they invested the CDH are animal husbandry with a total of 60.94%, followed by commerce with 19.27%, and 11.98% of the population invested in other economic activities such as agriculture, services, and manufacturing industry. Additionally, it is evident that 7.81% of the beneficiaries did not start enterprises and used the capital for other activities such as personal expenses. In conclusion, the manufacturing industry and agriculture provide income no higher than 5.75 % than the other activities, being these the enterprises that have less acceptance among the beneficiaries. Moreover, it is proved in statistical terms that it is indifferent to undertake any of the activities because it does not affect the economic benefit of the beneficiaries.